POTENSI PEMAKAIAN BERBAGAI MACAM MEDIA TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI (Oryza sativa L.) DENGAN SISTEM AKUAPONIK VERTIKULTUR - Maimunah Siregar; Najla Lubis; Andri Ramadhan (Fakultas Pertanian, Universitas Janabadra, 2023)
Aquaponics is a plant cultivation technique that is integrated with the cultivation of aquatic animals such as fish. The aim of the study was to determine the potential use of various growing media on the growth and production of rice (Oryza sativa L.) in a verticulture aquaponics system. This study used a non-factorial Completely Randomized Design (CRD), with 4 treatments and 5 replications so that there were 80 research sample units. The factor studied was the use of several types of planting media in the